Analisis Manajemen Perubahan UMKM Pada Saat Pandemi Covid-19 (Studi Zieffa Bakery) - Putri Salsa Nabila; Nuri Aslami (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
ThisQCovid-19QpandemicQwill haveQa significant impact on MSMEs, this is due to restrictionsz on businessqoperations andzreduced sales and loss of market share as a result of the enactment of PSBBz so that people limit activities outside the home. This study aims to find out how to manage changes that occur in MSMEs during the covid-19 pandemic. The type of research conducted is a type of descriptive qualitative research in which the data collection technique used in this study is in the form of interviews. The results of this study indicate that in the current COVID-19 pandemic conditions, Zieffa Bakery has experienced a drastic change in sales, especially since the PSBB was implemented to prevent the spread of the Covid-19 virus because people are required to work, worship, and study from home causing changes in consumption behavior. public. Furthermore, the marketing system is difficultzin a pandemic becausezin the midst of the Covid-19 pandemic, MSMEs are required to change their marketing strategy from offline to online in order to maintain their economy.